Stres Kerja, Insentif, Kepuasan Pengguna Bepengaruh terhadap Kinerja Sistem Informasi Akuntansi - Pragaswari, Destha Della; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p13, 2020)
The accounting information system can enable the duplication of tasks experienced by employees to cause work stress, incentives that are not in accordance with the workload and the user's dissatisfaction with the information system used. Purpose of study are to determine the effect of work stress, incentives, user satisfaction on the performance of accounting information systems. The sample is the employee who uses the accounting information system in Bapenda Denpasar.  purposive sampling is used with 60 respondents and analyzed by multiple linear regression. This study found, work stress variables can reduce the performance of accounting information systems, incentives and user satisfaction can improve the performance of accounting information systems. 58.2% variation in accounting information system performance is influenced by all three independent variables and 41.8% is influenced by other factors. Keywords: Job Stress; Incentives; User Satisfaction; Accounting Information System Performance.